Application System Model for the Division of Technician Tasks at PT. Sari Coffee Indonesia Jakarta - Purwanti Purwanti; Dian Nazelliana (Journal of Artificial Intelligence and Innovative Applications (JOAIIA), 2022)
The purpose of this study was to determine the weaknesses and shortcomings of the technician application system at PT. Thus, Sari Coffee Indonesia Jakarta can design an application that will improve the application system that is currently running. The researcher hopes that the application that will be made will be useful for the company so that it supports employee performance and can provide benefits for the Sari Coffee Indonesia company. The research method used is Grounded (Grounded research) which is a research method based on facts and using analysis in the field with the aim of knowing the information system process for the division of technician tasks carried out within the scope of PT. Sari Coffee Indonesia. Keywords: System Model, Task division system, DAD